Factors that influence peritonitis events on patients with continuous ambulatory peritoneal dialysis in Sanglah General Hospital, Denpasar-Bali, Indonesia - Gede Wirya Kusuma Duarsa; Oka Udrayana; Yeni Kandarini; Raka Widiana; Marleen (Neurologico Spinale Medico Chirurgico, 2020)
Background. To determine risk factors that influence peritonitis event on patients with Continuous Ambulatory Peritoneal Dialysis (CAPD) in Sanglah Hospital, thus, we can prevent the occurrence of peritonitis in CRF patients with CAPD. Methods. This is a retrospective cohort study, which was conducted at the Sanglah Hospital in Denpasar from August to September 2016. All data are processed using SPSS 17.0 for Windows, data analysis by using the Kaplan Meier (K-M) curves, hypothesis using the log-rank test, while for the survival is by using the median or mean survival. The significance is determined by the value of p < 0.05 with 95% CI. Results. A total of 78 people (46 men and 32 women) who meet the inclusion criteria of this study. Thirteen people (16.7%) are experiencing peritonitis. K-M Survival Curves between in CRF patients with CAPD, with Age ≥ 50 years (51.36 months survival rates, 95% CI 44.79 until 57.93) with < 50 years (56.1 months Survival rates, 95% CI 51.41 until 60.78) with RR 2.54 log-rank p 0.084. K-M Survival Curves between in CRF patients with CAPD, with DM (mean 52.63 months survival rates, 95% CI 47.21 until 58.06) with No DM (56.88 months survival rates, 95% CI 52.89 until 60.88) with RR 4.16 and 0.037 log-rank p. Conclusion. There is a correlation between DM and the incidence of peritonitis in CRF patients with CAPD at Sanglah Hospital. However, age and education level are not related.